Penerapan Supply Chain Management Di PT Brataco Chemical Cabang Medan - Somadi; Vica Mariani S (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2021)
The research objective was to determine the application of Supply Chain Management (SCM) at PT Brataco Chemical Medan Branch. This research used a descriptive approach with SCM analysis. Based on the research results, the company's suppliers consist of suppliers of main and supporting raw materials. Purchases of raw materials are made by pre-order with a credit payment system. Incoming raw materials will be checked with order data. If the item does not match the order, it will be returned to the supplier for replacement. Meanwhile, the appropriate goods will be placed in the warehouse and then the production process is carried out. The production process is carried out in two stages, namely the first stage to produce low TDS & nearly neutral PH and the second stage to produce Aqua Demineralization. The production results are then checked for conformity with the predetermined standards. Products that pass will be distributed to consumers using a car provided by the company. Orders that do not fit or are defective, then consumers can return to the company to be replaced with new goods.